Another note on smooth numbers in short intervals - Matomaki K (WORLD SCIENTIFIC PUBL CO PTE LTD, 2022)
In this paper, we prove that, for any positive constants d and e and every large enough x, the interval [x, x + root x(log x)(7/3+delta)] contains numbers whose all prime factors are smaller than x(epsilon).